A Method for Directing Collaborative Study Guide Construction by Undergraduate Student Groups - Maureen Lynn Petrunich-Rutherford (Indiana University Office of Scholarly Publishing, 2021)
Students often request study guides; however, the impact of study guides on student learning is mixed. Here, some evidence on student study guide usage and collaborative learning is briefly reviewed. This information helped to shape the development of a collaborative activity where student groups create their own study guide questions based on the chapter learning outcomes. Requiring students to collaborate and create their own study guides may encourage a higher engagement with and deeper processing of the course content.